Niveles de ansiedad y trastornos temporomandibulares en pacientes atendidos en la IPRESS 1 - 3 San Antonio de Iquitos 2022 - Navarro Gonzales, Susana (2023)
The object of study was to indicate the relationship between Anxiety Levels and Temporomandibular Disorders (TMD) in patients treated at the IPRESS I-3 San Antonio, 2022. The research was quantitative, the design was non-experimental, correlational, cross-sectional. The proportion of the population group was 366 individuals treated in the dental area of the establishment. Anxiety Inventory, Trait-State (IDARE) and the Research Diagnostic Criteria (CDI) instrument for TTM were used. The most notable results were: there was a statistically significant association between age and Temporomandibular Disorders (p=0.003). In marital status, married people exhibited a statistically significant association with Temporomandibular Disorders (p=0.009), highlighting myalgia. The prevalence of TMD at the San Antonio Health Center was high (68.2%). The average level prevailed in both Anxiety-Trait and Anxiety-State. Myalgias predominated in the diagnoses of Temporomandibular Disorders. Finally, it was inferred that there is a relationship between Temporomandibular Disorders, Anxiety-State and Anxiety-Trait (p=0.000).